PENILAIAN KINERJA UMKM SAAT PANDEMI COVID-19 (STUDI KASUS UMKM RUMAH WARNA) - Chivalrind Ghanevi Ayuntari; Astrid Kanadya Maher (Bajang Institute, 2023)
Financial performance is a measure of the condition from ability of a business in financial point of view of the business. By measuring financial performance, it can help a business to know the condition of its business. Measurement using profitability ratios in analyzing the company's financial performance through financial statements can produce important information in the form of how much the company generates on the resources used. The financial statements used are in 2020 and 2021 for comparison. The results showed that Rumah Warna experienced a decrease in performance in 2021 compared to the previous year (2020). This was due to several factors that occurred inside and outside the company.